Holistic Approach in Islamic Education to Improve Mental Health - Karimullah, Suud Sarim (Lembaga Penelitian Dan Publikasi Ilmiah (LPPI) Yayasan Almahmudi Bin Dahlan, 2023)
This study explores the influence of a holistic approach in Islamic education on improving mental health. This study is a type of literature research with a critical literature analysis approach to various literature sources relevant to the topic of study, such as books, scientific journals, articles, conference papers, and other digital sources. The study results stated that a holistic approach in Islamic education is a relevant and effective solution to improving students' mental health. Integrating physical, emotional, social, intellectual, and spiritual aspects can help students cope with life's pressures and challenges, improve self-esteem, and better understand their emotions. Implementing this holistic approach requires active support from all parties, including educational institutions, teachers, parents, mental health professionals, and society. By overcoming various challenges and optimizing existing potential, a holistic approach in Islamic education can be an essential vehicle in shaping a healthier, stronger, and more competitive young generation for a better future.